Meta-analysis on efficacy and safety of new oral anticoagulants for venous thromboembolism prophylaxis in elderly elective postarthroplasty patients. Issue 8 (December 2015) - Pathak, Ranjan; Giri, Smith; Karmacharya, Paras; Aryal, Madan Raj; Poudel, Dilli Ram; Ghimire, Sushil; Jehangir, Asad; Shaikh, Bilal; Rettew, Andrew; Donato, Anthony A.
Abstract : The risk of venous thromboembolism (VTE) increases with age. New oral anticoagulants (NOACs) have been increasingly studied for VTE prophylaxis in patients with elective postarthroplasty. Although the elderly population accounts for a significant proportion of patients requiring VTE prophylaxis, safety and efficacy of NOACs in this subgroup for VTE prophylaxis has not been well studied. Relevant studies were identified through electronic literature searches of MEDLINE, EMBASE, Cochrane Library, and ClinicalTrials.gov (from inception to 12 August 2014). Phase III randomized controlled trials that compared NOACs against low-molecular-weight heparin (LMWH) in the prevention of VTE prophylaxis in patients with elective postarthroplasty were included. We defined our elderly population as adults of at least 75 years and assessed the reported safety and efficacy outcomes with NOACs in this population. Study-specific odds ratios (ORs) were calculated and between-study heterogeneity was assessed using the I 2 statistic. In nine trials involving 29 403 patients, the risk of VTE or VTE-related deaths in elderly patients with elective postarthroplasty was similar with NOACs compared with LMWH (OR 0.62, 95% confidence interval 0.30–1.26; P = 0.18; I 2 = 44%) but bleeding risk was significantly lower (OR 0.71, 95% confidence interval 0.53–0.94; P = 0.02; I 2 = 0%). Analysis of individual NOACs showed superior efficacy but similar safety for apixaban when compared with LMWH. Efficacy and safety profiles of rivaroxaban and dabigatran were similar to LMWH. In elderly patients with elective postarthroplasty, NOACs have similar efficacy but superior safety when compared with enoxaparin for VTE prophylaxis. Abstract : Supplemental Digital Content is available in the text